1979
DOI: 10.1016/0005-2736(79)90269-4
|View full text |Cite
|
Sign up to set email alerts
|

A possible role of rhodopsin in maintaining bilayer structure in the photoreceptor membrane

Abstract: Summary31p-NMR measurements demonstrate that at 37 ° C, independent of the photolytic state of the photopigment rhodopsin, the lipids in the photoreceptormembrane are almost exclusively organised in a bilayer. In strong contrast, the 31P-NMR spectra of the extracted lipids are characteristic for the hexagonal HII phase and an isotropic phase. The isotropic phase is characterised by freeze-fracture electron microscopy as particles and pits on smooth surfaces, possibly indicating inverted micelles. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
21
2

Year Published

1980
1980
1997
1997

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 31 publications
(28 reference statements)
8
21
2
Order By: Relevance
“…branes as comparable 3~P-NMR spectra and freeze-fracture morphology were observed in the total lipid extracts of rod outer segment [9] and Escherichia coli membranes [10]. Furthermore 3~p-NMR spectra of microsomes at 37"C indicate isotropic motion of part of the membrane phospholipids [11,19].…”
Section: Pc Noordam Et Al Barrier Characteristics Of Merabrane Modementioning
confidence: 69%
“…branes as comparable 3~P-NMR spectra and freeze-fracture morphology were observed in the total lipid extracts of rod outer segment [9] and Escherichia coli membranes [10]. Furthermore 3~p-NMR spectra of microsomes at 37"C indicate isotropic motion of part of the membrane phospholipids [11,19].…”
Section: Pc Noordam Et Al Barrier Characteristics Of Merabrane Modementioning
confidence: 69%
“…It is therefore certainly possible that some proteins play structural bilayer~tabflizing roles, as has been suggested for rod outer segment membranes [26]. This possibility is reinforced by recent studies [27] indicating an asymmetric distribution of phospholipids across the inner mitochondrial membrane, with an enrichment of phosphatidylethanolamine and cardiolipin in the inner monolayer.…”
Section: Discussionmentioning
confidence: 84%
“…It is also possible that this is due to an indirect effect of the presence of rhodopsin or opsin on the lipid membrane matrix. It has previously been shown that rhodopsin and opsin stabilize the lamellar structure of the rod outer segment disk membrane (de Grip et al, 1979;Albert et al, 1984) and this could affect the denaturation of neighboring opsins.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal stabilities of membrane-bound and detergentsolubilized rhodopsin and opsin have been investigated previously (Hubbard, 1958;de Grip, 1982;Fong et al, 1982). Hubbard (1958) showed membrane-bound rhodopsin to be considerably more stable than opsin by determining the amount of rhodopsin (or opsin) that survived heating for 10 min at various fixed temperatures.…”
mentioning
confidence: 99%